Outcome of Open Pyeloplasty on Ipsilateral Renal Function - Rahman, Hamudur; Islam, Md Sayedul; Chowdhury, Md Golam Mowla; Islam, AKM Anwarul; Shameem, Isteaq Ahmed (Bangladesh Journal of Urology, 2020)
Objective: The objective of this study is to determine the ipsilateral renal function after open pyeloplasty. Patients and methods: The study comprises 50 patients with ultrasonographically and urographically demonstrated hydronephrosis and primary pelvi-ureteric junction obstruction for reconstructive surgical treatment at urology department of Bangabandhu Sheikh Mujib Medical University Hospital between January 2012 and September 2013. Anderson- Hynes pyeloplasties were performed in 50 patients. Data were collected by interview, review of records and documents in data collection sheet. Data were analyzed by using paired t-test. Level of significance was set at 5%(P<0.05). Statistical analysis done by SPSS (SPSS Inc. Chicago, IL, USA), version 16.0.0. Results: The male and female ratio was1: 0.33. Mean age of the patients was 7.35 years. Left and right side ratio was 1.5: 1. The mean ± SD of pre operative cortical thickness was 3.67 ± 0.91 and post operative thickness after 1 month, 3 months, 6 months and 12 months were 3.95 ± 0.91, 4.61 ± 1.18, 4.61 ± 1.18, 5.15 ± 1.31 and 6.22 ± 1.37 respectively. The mean ± SD of split renal function were 24.22 ± 3.42 and 29.14 ± 4.20 in pre operative and post operative respectively. The mean ± SD of split GFR were 25.38 ± 4.11and 34.47 ± 6.30 in pre operative and post operative respectively. Renal functional status was seen as improvement in 39, stable in 3, and deterioration in 2 patients. Conclusions: When dealing with patients with pelviureteric junction obstruction, surgical treatment should be undertaken in patients with symptoms and/or impaired renal function. Bangladesh Journal of Urology, Vol. 18, No. 1, Jan 2015 p.28-32